Spin dynamics in Na4-xIr3O8 (x = 0.3 and 0.7) investigated by 23Na NMR and μsR - Balodhi, A.; Singh, Yogesh (Institute of Physics Publishing, 2015)
We report 23Na nuclear magnetic resonance (NMR) and zero-field (ZF) and longitudinal-field (LF) muon spin relaxation (μSR) measurements of the depleted hyperkagome compounds Na4−xIr3O8 (x  =  0.3 and 0.7), which undergo an insulator-semimetal transition as a function of x. The 23Na spin-lattice relaxation rates, $T_{1}^{-1}$ , follow a T2.5 power law behavior at accessible temperatures of T  =  120–350 K. A substantial temperature dependence of $T_{1}^{-1}$ indicates the presence of gapped excitations at elevated temperatures through the transition to a semimetallic phase. ZF-μSR results reveal that hole-doping leads to a melting of quasi-static order to a dynamically fluctuating state. The very slow muon depolarization rate which varies hardly with temperature indicates that spins are close to an itinerant limit in the largest doping x  =  0.7. The dynamic relaxation rates extracted from the LF-μSR spectra show a three-dimensional diffusive transport. Our combined NMR and μSR results suggest the occurrence of intriguing spin and charge excitations across the insulator-semimetal transition.
Only IISERM authors are available in the record.
Keywords: Spin dynamics; Na4−xIr3O8; x = 0.3 and 0.7; 23Na NMR and μSR